2005
DOI: 10.1104/pp.105.070763
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transformed Arabidopsis with Altered Alternative Oxidase Levels and Analysis of Effects on Reactive Oxygen Species in Tissue  

Abstract: The alternative oxidase (AOX) of plant mitochondria transfers electrons from the ubiquinone pool to oxygen without energy conservation. AOX can use reductant in excess of cytochrome pathway capacity, preventing reactive oxygen species (ROS) formation from an over-reduced ubiquinone pool, and thus may be involved in acclimation to oxidative stresses. The AOX connection with mitochondrial ROS has been investigated only in isolated mitochondria and suspension culture cells. To study ROS and AOX in whole plants, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
240
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(260 citation statements)
references
References 94 publications
13
240
2
5
Order By: Relevance
“…However, it has also been reported that succinate-dependent mH 2 O 2 production is faster than pyruvate/malate-dependent mH 2 O 2 production in plants, indicating that Complex II has a larger role than Complex I (40). Additionally, the ubiquinone pool itself has been highlighted as a site of ROS production in plant mitochondria (41).…”
Section: Identification Of An Arabidopsis Mutant With Altered Stressmentioning
confidence: 99%
“…However, it has also been reported that succinate-dependent mH 2 O 2 production is faster than pyruvate/malate-dependent mH 2 O 2 production in plants, indicating that Complex II has a larger role than Complex I (40). Additionally, the ubiquinone pool itself has been highlighted as a site of ROS production in plant mitochondria (41).…”
Section: Identification Of An Arabidopsis Mutant With Altered Stressmentioning
confidence: 99%
“…A, Regulation of ROS-related TF in the O 2 deprivation microarray experiments. B, Regulation of HsfA2, ZAT12, ZAT6, and ADH1 gene in wild-type and rbohD 2 plants under anoxia in a time course up to 8 h. A 6h 1 , 6 h of anoxia treatment without or with 90 mM Suc (s) added before the treatment (Loreti et al, 2005); A 6h 2 , 6 h of anoxia treatment (Banti et al, 2010); A 12h, 12 h of anoxia treatment, total and polysomal (p) RNA (Branco-Price et al, 2005); H 4h, 4 h of hypoxia treatment at 1% O 2 (Licausi et al, 2010); S 7/24h, 7 and 24 h of submergence treatment (Loreti et al, 2005); A 6h 2 , 6 h of anoxia treatment (Banti et al, 2010); A 12h, 12 h of anoxia treatment, total and polysomal (p) RNA (Branco-Price et al, 2005); H 4h, 4 h of hypoxia treatment at 1% O 2 (Licausi et al, 2010); S 7/24h, 7 and 24 h of submergence treatment ; flu 0.5 (30')/1/2h, flu mutant shift from dark to light (op den Camp et al, 2003); AOX1a-AS, AOX1a-AS mutant (Umbach et al, 2005) heat shock in Arabidopsis cell (Rikhvanov et al, 2007). Moreover, in mammals' pulmonary arteries hypoxiadriven mitochondrial ROS production has been suggested to trigger NADPH oxidase activity, suggesting a mechanism by which mitochondria and cytosol both contribute to the increase in ROS production during low O 2 (Rathore et al, 2008).…”
Section: Atrbohd Helps Mediate Ros Signaling In Seedlings/shoots Undementioning
confidence: 99%
“…This alternative pathway is nonphosphorylating, resistant to cyanide and antimicine and inhibited by salicilhydroxamic acid (SHAM) and n-propyl gallate (Schonbaum et al, 1971;Siedow and Grivin, 1980). It has been the focus of many studies in plant respiratory metabolism under several environmental stresses, mainly because an increased AOX capacity might contribute to controlling the formation of reactive oxygen species (ROS) (Wagner, 1995;Popov et al, 1997;Maxwell et al, 1999;Umbach et al, 2005 (Li and Staden, 1998). These ROS may initiate destructive oxidative process such as lipid peroxidation, chlorophyll bleaching, protein oxidation, and damage to nucleic acids (Scandalios, 1993).…”
Section: Introductionmentioning
confidence: 99%